Survey on Recent Ulam Stability Results Concerning Derivations. (8th August 2016) - Brzdęk, Janusz; Cădariu, Liviu; Ciepliński, Krzysztof; Fošner, Ajda; Leśniak, Zbigniew
Abstract : This is a survey presenting the most significant results concerning approximate (generalized) derivations, motivated by the notions of Ulam and Hyers-Ulam stability. Moreover, the hyperstability and superstability issues connected with derivations are discussed. In the section before the last one we highlight some recent outcomes on stability of conditions defining (generalized) Lie derivations.